Innovative agroecology practices improve maize and bean yields in nutrient-deficient sandy soils of Makueni, Kenya - Bolo, Peter; Korir, Hezekiah; Adoyo, Beatrice; Kuria, Anne; Fuchs, Lisa Elena (2024)
Agroecology has been highlighted as a sustainable approach with the potential to support food system transformation in both low and middle-income countries. Its potential to improve soil and crop productivity is unmatched. Implementation of innovative agroecology practices is key in promoting soil quality and health, improving agrobiodiversity and enhancing crop productivity.